Energy metabolism disorders and potential therapeutic drugs in heart failure - Yanan He; Wei Huang; Chen Zhang; Lumeng Chen; Runchun Xu; Nan Li; Fang Wang; Li Han; Ming Yang; Dingkun Zhang (Elsevier, 2021)
Heart failure (HF) is a global public health problem with high morbidity and mortality. A large number of studies have shown that HF is caused by severe energy metabolism disorders, which result in an insufficient heart energy supply. This deficiency causes cardiac pump dysfunction and systemic energy metabolism failure, which determine the development of HF and recovery of heart. Current HF therapy acts by reducing heart rate and cardiac preload and afterload, treating the HF symptomatically or delaying development of the disease. Drugs aimed at cardiac energy metabolism have not yet been developed. In this review, we outline the main characteristics of cardiac energy metabolism in healthy hearts, changes in metabolism during HF, and related pathways and targets of energy metabolism. Finally, we discuss drugs that improve cardiac function via energy metabolism to provide new research ideas for the development and application of drugs for treating HF.